Innate Immunity Modulation by the IL-33/ST2 System in Intestinal Mucosa. (4th December 2012) - García-Miguel, Marina; González, M. Julieta; Quera, Rodrigo; Hermoso, Marcela A.
Abstract : Innate immunity prevents pathogens from entering and spreading within the body. This function is especially important in the gastrointestinal tract and skin, as these organs have a large surface contact area with the outside environment. In the intestine, luminal commensal bacteria are necessary for adequate food digestion and play a crucial role in tolerance to benign antigens. Immune system damage can create an intestinal inflammatory response, leading to chronic disease including inflammatory bowel diseases (IBD). Ulcerative colitis (UC) is an IBD of unknown etiology with increasing worldwide prevalence. In the intestinal mucosa of UC patients, there is an imbalance in the IL-33/ST2 axis, an important modulator of the innate immune response. This paper reviews the role of the IL-33/ST2 system in innate immunity of the intestinal mucosa and its importance in inflammatory bowel diseases, especially ulcerative colitis.